2015
DOI: 10.1177/0957650915624034
|View full text |Cite
|
Sign up to set email alerts
|

Design of volute shape of centrifugal fans

Abstract: This work addresses the issues of decreased efficiency and static pressures of a centrifugal fan under variable working conditions (VWCs). A design method for the volute radius with flow-correcting coefficients and an area factor was proposed. The model of the design method was solved using genetic algorithms in MATLAB. The volute was designed for two cases: with area constraints and without area constraints. Computational fluid dynamics was used in the numerical simulations of the original fan and the two oth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 24 publications
0
5
0
Order By: Relevance
“…The designer also needs to determine in advance the desired cross-sectional shape of the volute which can affect the overall dimensions of the volute and may affect the flow losses inside the volute. As only the top wall of the volute will be solved from equation (5), the boundary on both sides of the volute (the side walls), which are shared by all the cross-sections, should be given before the design can be started. If the volute is a twin-entry type used in turbocharging turbines, the central dividing wall of the two branches shall also be described.…”
Section: Boundary Conditions and Input Parametersmentioning
confidence: 99%
See 2 more Smart Citations
“…The designer also needs to determine in advance the desired cross-sectional shape of the volute which can affect the overall dimensions of the volute and may affect the flow losses inside the volute. As only the top wall of the volute will be solved from equation (5), the boundary on both sides of the volute (the side walls), which are shared by all the cross-sections, should be given before the design can be started. If the volute is a twin-entry type used in turbocharging turbines, the central dividing wall of the two branches shall also be described.…”
Section: Boundary Conditions and Input Parametersmentioning
confidence: 99%
“…The numerical method is required to solve the dimensionless form of equations (2)(3)(4)(5). A two-dimensional mesh is proposed and is shown in Figure 1.…”
Section: Numerical Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…In the work of Baloni et al, 20 the performance of centrifugal blower is enhanced with an optimization process on the volute using Taguchi method and ANOVA approach. Lv et al 21,22 found that the volute width should be comprehensively determined according to other parameters. An appropriate width could improve the uniformity of the flow field within the fan and the fan performance.…”
Section: Introductionmentioning
confidence: 99%
“…Jiang et al [6] studied the influence of the cut volute profile on the aerodynamic and acoustic performances of the fan by experiment, which is useful for causing a flow structure of the impeller across near the second clearance and re-organizing the circumference distribution of the impeller flow status. Lv et al [7] proposed a design method for the volute radius with a flow-correcting coefficient and area factor-the volute is designed with or without area constraint. The results showed that the 2 of 23 efficiency and static pressure of the two designed fans were improved.…”
Section: Introductionmentioning
confidence: 99%